The determinants of Islamic and conventional banking profitability in Asian countries / Nurhafiza Abdul Kader Malim and Sarini Azizan - Abdul Kader Malim, Nurhafiza; Azizan, Sarini (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2020)
This paper aims to examine the determinants of Islamic and conventional banking profitability in Asian countries. We estimated an econometric model using the Generalized Method of Moments (GMM) from 2009 to 2013 based on 162 conventional banks and 65 Islamic banks operating in a dual banking system. This paper extends prior literature by examining the profitability of Islamic banks and conventional banks using the more comprehensive determinants, especially in Asian countries where studies are observably limited. The results show that the factors influencing the profitability of Islamic and conventional banks are different. The profitability of Islamic banks is significantly affected by the size, management efficiency, inflation, market concentration, the rule of law and monetary freedom. For conventional banks, the key determinants include capital, size, credit risk, management efficiency, monetary freedom and economic growth. The findings provide policy implications for enhancing the profitability in a dual banking system.